Vergi denetiminde analitik inceleme prosedürleri ve örnek uygulama - Gül, Şakir Ercan (My University, 2003)
The major source of income for the state consists of taxes. Since these taxes depend on the system of declaration, the correct amount of taxes dependes on the sensitivy of taxpayers and their realistic declarations. Therefore, the state has got the power of control over the taxpayers' accounts to understand whether they give the correct declaration or not. There are many technicques used for tax control. Today, analitical tax auditing, which are used by managing directors and financial institutions, has become one of the techiniques of tax control. The use of analitical auditing procedures for tax control helps the controller who is going to study the taxpayers' declaration. With the use of analitical auditing procedures for tax control, the signals of tax evasion and tax loss will better be fixed. Consequently, this will enable the tax controller to see which points to emphasize in terms of tax control.
Keywords: Hukuk; Vergi Denetimi; Vergi hukuku